A Critical View on the Intensified Adjectives in Turkish - Ebru Koç (Ana Dili Eğitimi Dergisi, 2018)
The aim of this research is to investigate the tendency of native speakers of Turkish when intensifying adjectives in Turkish and examine whether there is a rule that governs which of the consonants (m, p, r, or s) are used in intensifying adjectives. The participants of the study were 190 native speakers of Turkish whose ages ranged from 18 to 56. A list containing 21 adjectives was used to collect data. The data were analyzed in terms of the frequencies of usage. The results showed that in intensifying the 21 adjectives in the list, ‘p’ was the most frequently used consonant, and ‘r’ was the least frequently used consonant. Another significant finding of the study was that most of the adjectives seemed to have more than one intensified form.